Burkina Faso : "Literacy for the Little Ones" in Nomgana - Easton, Peter (World Bank, Washington, DC, 2012)
Nomgana is the hub community of a very active inter-village federation in Burkina Faso. In recent years, a local association called Manegbzanga has launched an experimental program using Moore language literacy as the basis for learning French. The program achieved a good deal of success and was soon faced with increasing demand for enrollment from young people who had missed primary schooling or had been forced to drop out. Test results showed that the pupils at the center were ahead of those at the area's formal primary school in some subjects. However, there were several handicaps in the center: 1) the rigidity of pre-established schedules and time allocations to different subject matters required for accreditation in the formal system worked against some of the things that the Nomgana center was experimenting. 2) Some of the content of French textbooks turned out to be quite inappropriate for use once translated into Moore. 3) To match the rhythm and requirements of the official curriculum the teaching staff had to largely abandon instruction directly in Moore, despite the fact that some of the most encouraging learning results were appearing in classes taught in the mother tongue.